2019
DOI: 10.1371/journal.pone.0223092
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill patients with community-onset intraabdominal infections: Influence of healthcare exposure on resistance rates and mortality

Abstract: The concept of healthcare-associated infections (as opposed to hospital-acquired infections) in intraabdominal infections (IAIs) is scarcely supported by data in the literature. The aim of the present study was to analyse community-onset IAIs (non-postoperative/non-nosocomial) in patients admitted to intensive care units (ICUs), to investigate differences in resistance patterns linked to healthcare exposure and mortality-associated factors. A one-year prospective observational study (17 Spanish ICUs) was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Pupelis et al [19] reported a little bit higher value than ours -9.4% in patients with LP. Maseda et al [20] observed a death rate of 11.1% in critically ill patients with LP. The highest mortality rate was reported by Blot et al [7] in critically ill patients with LP -24.2%.…”
Section: Discussionmentioning
confidence: 97%
“…Pupelis et al [19] reported a little bit higher value than ours -9.4% in patients with LP. Maseda et al [20] observed a death rate of 11.1% in critically ill patients with LP. The highest mortality rate was reported by Blot et al [7] in critically ill patients with LP -24.2%.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, Bagshaw et al concluded that age ≥80 years, regardless of the ICU admission diagnosis, was associated with higher ICU and hospital mortality compared to younger patients [2]. Previous studies suggested that advanced age is a contributing factor for death in patients with secondary peritonitis as well as in critically patients with community-onset intra-abdominal infection [7,16]. Recently, Martin-Loeches at al.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal infections and in particular complicated intra-abdominal infections are difficult to treat. They differ from other severe infections in complexity of identification and diagnosis, diversity of etiology, degree of severity and need for source control [7][8][9][10][11][12][13]. Moreover, the increasing prevalence of multidrug resistant (MDR) bacteria challenges the appropriateness of empiric antibiotic therapy thereby increasing the risk for adverse outcomes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of inflammatory mediators, hypercatabolism, impaired coagulation, systemic and visceral blood flow disorders, damage of enterocytes develops rapidly, almost all functions of the digestive tract are disrupted -barrier, metabolic, immunoreactive, endocrine, etc. Intestinal insufficiency is a key moment in the development of the "vicious" circle in AP and AS, because the translocation of microorganisms and their toxins supports the general inflammatory reaction, aggravating metabolic disorders [17][18][19].…”
Section: Introductionmentioning
confidence: 99%